Visiting the Past as a Way to the Future: Virtual Environments for Social Memory Construction - Worden, Suzette (Curtin University of Technology, 2007)
In considering the future it is often necessary to re-visit the past. New communication and visualisation technologies have enhanced the ability of individuals and groups to create narratives to portray ideas about the past. Museums in particular have created projects about the past that offer rewarding experiences for their audience in all kinds of contexts. However, in the last few years the results of these activities have moved from being called 'histories' to being called accounts of cultural or social memory, where museums and libraries have become memory institutions. This paper will examine how traces of the past can be brought together to inform the future and whether this emphasis on memory denotes a more active and participatory role for those who are involved as visitors or 'users' of digital resources.The first part of this discussion is a theoretical examination of history making and within that process, how ideas about physical environments relate to virtual spaces that are created to support the 'memory institution.' Local/global communication and interchange is discussed in detail in the context of migration. This shows how records of the movements of people across continents and between nations are constructed and deconstructed, how far such accounts need to make reference to material objects within the physical landscape, and how constructions of place are layered, destroyed, permanent or transient.In order to explore migration in detail, a project that explores memory traces between mining heritage in Cornwall, UK and Western Australia is discussed to show what aspects of past mining heritage can meaningfully be connected to aspects of present economic growth. It is proposed that memory institutions need to provide a rich experience for social memory to be constructed; where 'history' might have many ways of telling and is fluid and re-traceable.